Low-Temperature Fabrication of Flexible Dye-Sensitized Solar Cells: Influence of Electrolyte Solution on Performance under Solar and Indoor Illumination - Roberto Avilés-Betanzos; Gerko Oskam; Dena Pourjafari (Energies, 2023)
Flexible photovoltaics is an attractive technology for product-integrated energy supply under both outdoor and interior conditions. In particular, dye-sensitized solar cells (DSSCs) based on flexible plastic conductive substrates provide ample opportunities for unique applications; however, they prevent the use of high-temperature processing steps usually applied in the fabrication of the solar cell. In the first part of this paper, we present an overview of a careful selection of the most relevant work in the field of flexible DSSCs (F-DSSCs), ranging from pioneering methodsto the most cutting-edge techniques. Key elements and critical considerations for the design of an efficient F-DSSC are also provided. In the second part, we report the fabrication of DSSCs on both rigid and flexible plastic substrates using low-temperature processing. Three different I−/I3− electrolyte configurations were tested. Rigid and F-DSSC showed 2.62% and 1.00% efficiency under 1 sun and an output power of 8.60 and 4.00 μW/cm−2 under low-light conditions, respectively. In this work, we report a novel solvent mixture that shows a significant enhancement of the performance of the low-temperature processed configuration, without adding steps in the fabrication process.